LitPOS – a part of EUPOSS® - Parseliunas, Eimuntas; Buga, Arunas; Marozas, Leonardas; Petniunas, Marius; Urbanas, Saulius (Geodesy and Cartography, 2012)
LitPOS, the network of permanent reference GNSS stations, is to start operation in July 2007. It will provide data both for real-time and post-processing applications. LitPOS stations cover the all territory of Lithuania. Total number of GNSS stations is 25, therefore the integration of some stations of neighbouring countries is foreseen. It is possible on the basis of cooperation in EUPOS® project. Th e European Position Determination System (EUPOS®) project is an initiative and cooperation of currently 15 Central and Eastern European countries (CEE) and two-German states that build up a ground based on European regional GNSS augmentation system with uniform standards that will cover a territory of about 10 million square kilometers. EUPOS® provides a high-quality diff erential GNSS information for high precise positioning and navigation usable in a large fi eld of applications. To enlarge the EUPOS® activities transcending technical realizations the project EUPOS® – Interregional Cooperation (EUPOS®-IRC) was launched on October 2006, since it is accepted as a European Union INTERREG IIIC Programme operation. Main aims of this operation are to identify, point out and enable possibilities and benefi ts of the use and application of GNSS technology in the fi eld of regional development, to establish a long-lasting cross-border cooperation between experts in the fi eld of GNSS and geoinformation, on the one hand, and regional policy experts and stakeholders, on the other hand. LitPOS – EUPOS® DALIS Santrauka. Straipsnyje analizuojama LitPOS (Lietuvos padėties nustatymo sistema) sandara, pateikiama techninės ir programinės įrangos schemos bei duomenų srautai. LitPOS – nuolat veikiančių GNPS stočių tinklas – pradėjo veikti 2007 m. liepą. Jis teikia informaciją ir realiuoju laiku, ir duomenims apdoroti po matavimų. 25 LitPOS stotys išdėstytos po visą Lietuvos teritoriją. Numatyta į tinklą įtraukti ir kaimyninių valstybių analogiškas stotis. Tokia galimybė įmanoma bendradarbiaujant EUPOS® projekte. Europos padėties nustatymo sistemos (EUPOS®) projekte bendradarbiauja 15 Centrinės ir Rytų Europos valstybių. Projekto tikslas – įrengti vientisą GNPS stočių tinklą, atitinkantį bendruosius standartus. EUPOS® teiks kokybišką didelio tikslumo GNPS informaciją taškų padėtims nustatyti ir navigacijai, taikomai įvairiose srityse. First published online: 03 Aug 2012